Decoding Glycobiomarkers in Non-Alcoholic Steatohepatitis (NASH) and Related Hepatocellular Carcinoma (HCC) - Bansal, Savita; Burman, Archana; Sen, Aparajita; Vachher, Meenakshi (Current Proteomics, 2024)
The incidence of Hepatocellular carcinoma (HCC) is rising at an alarming rate. It is now the third leading cause of cancer deaths worldwide. Non-alcoholic fatty liver disease (NAFLD) and its more aggressive form of non-alcoholic steatohepatitis (NASH) are emerging as significant risk factors for liver cirrhosis and HCC. Post-translational modifications in proteins especially glycosylation leading to the synthesis of glycoproteins have been implicated in carcinogenesis. Dysregulated glycoproteins and aberrant glycosylation patterns might contribute to the establishment of a protumorogenic environment in NAFLD/NASH patients leading to the establishment of hepatocarcinogenesis. Understanding the molecular mechanisms underlying the changes in glycosylation patterns of certain proteins would help in deciphering the role of glycoproteins in liver cancer and develop novel prognostic and diagnostic markers and therapeutic strategies for the successful treatment of HCC. Herein we discuss some important glycoproteins and altered glycosylation patterns that can be employed as biomarkers for the early detection of HCC in NASH and NAFLD patients.
Keywords: hepatocarcinogenesis